Ratio Decidendi Penjatuhan Putusan Bebas (VRIJSPRAAK) Dalam Pemalsuan Akta Otentik Oleh Notaris: Studi Putusan Nomor: 1216/Pid.B/2019/PN Jkt.Tim - Zhafira Amalia Irfanti (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Corruption is an extraordinary crime that causes state losses. Corruption is not only committed by individuals, but also by corporations. Problems that often arise in criminal acts of corruption committed by corporations are related to procedural law, especially related to proving corporate wrongdoing. In this regard, the author is interested in analyzing the evidence related to corruption committed by corporations in Decision No. 81/Pid.Sus/Tipikor/2018/PN.Jkt.Pst. This study discusses the problem of proving corruption committed by corporations and the judge's legal considerations in imposing a sentence on the Defendant. This study uses a normative juridical approach withresearch specifications prescriptive. This study also uses secondary data obtained through literature and documentaries and described systematically. The results of the study indicate that the criminal acts of corruption committed by corporations in Decision Number: 81/Pid.Sus/Tipikor/2018/PN.Jkt. evidenced by the suitability of evidence in the form of witness statements, expert statements, letters and statements from the defendant which proves that the defendant has fulfilled all the elements in the First Indictment, so that it has met the minimum limit of evidence, namely at least two valid pieces of evidence, the judge's conviction is obtained. that the defendant PT NKE was guilty of a criminal act of corruption. The basis for the judge's legal considerations is by taking into account the elements of the Articles of the First Indictment that have been fulfilled, namely by fulfilling the minimum limit of evidence and obtaining the judge's conviction, for which the Panel of Judges imposes a criminal sentence in the form of a principal penalty in the form of a fine and additional punishment in the form of payment of replacement money and the revocation of the defendant's rights to participate in the auction of government goods/services procurement.